Diseño e implementacion de un "food truck" furgón tipo combi independiente con anclaje a camioneta 4x4. - Barrionuevo Almeida, Carlos Xavier (2018)
The current economic situation of the Ecuador has reduced the labor market. It has enforced many people to create micro enterprises; food truck is an example of a micro enterprise. This study included a progressive development of different stages which starts from the analysis of market. It is designed to have implemented an industrial system suitable for a combi vehicle van and a profitable enterprise. A sample of 398 respondents discussed to promote, participate and evaluate the market. Fryer, griddle, lava crockery, table, refrigerator, water tank, tank for gas LPG, was implemented in draught to anchor a 4 x 4 truck system in order to develop the project. It the structure of the vehicle was modified to obtain a functional mechanism in correspondence to the health and safety ordinance of the Quito Metropolitan District. The design and construction of the mechanical components used different criteria such as: plates, slenderness, bending, deflection, stress and maximum effort. In order to validated the correct function of the mechanism, tests were running. In conclusion, the investment of the project was $7.673. Two people were employed. The return of the investment will be 24 months.